(untitled) (Journal Of Educational and Psychological Researches, 2011)
The objective of this research to identify the level of job satisfaction among lecturers Iraqi universities on the Law of University Service has determined the research community in the teaching staff or lecturers University (Baghdad, Mustansiriya, Technology, Al-Nahrean) were selected the same of them with a volume of (400) teaching (male and female) to complete the research has been prepared to identify composed of (49) items distributed on four axes and Search Results indicated that the level of job satisfaction among the teaching Iraqi university courses on the law of service is characterized by the presence of positive and job satisfaction and the law in general.